2012
DOI: 10.1021/jf302188a
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of Methylglyoxal by Curcumin in Cell-Free Systems and in Human Umbilical Vein Endothelial Cells

Abstract: Curcumin, the most active compound of curcuminoids, has been shown to inhibit formation of advanced glycation end products (AGEs) in streptozotocin-induced diabetic rats. However, little is known on whether curcumin may trap methylglyoxal (MGO), a major reactive dicarbonyl compound, to inhibit AGE formation. We found that one molecule of curcumin effectively trapped one molecule of MGO at a 1:3 ratio at 24 h of incubation under physiological conditions (pH 7.4, 37 °C). Curcumin decreased N(ε)-(carboxymethyl)ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Perhaps enolic form of heptadienone or pentadienone scaffolds of these synthesized compounds might act as an electron donor, which is very common mechanism for the scavenging activity of phenolic antioxidant to alter characteristics of glucose molecules 23 . Moreover, the hypoglycemic activities observed for these compounds were in agreement with previous findings on these analogues [24][25][26][27] .…”
Section: In Vitro Hypoglycemic Studiessupporting
confidence: 91%
“…Perhaps enolic form of heptadienone or pentadienone scaffolds of these synthesized compounds might act as an electron donor, which is very common mechanism for the scavenging activity of phenolic antioxidant to alter characteristics of glucose molecules 23 . Moreover, the hypoglycemic activities observed for these compounds were in agreement with previous findings on these analogues [24][25][26][27] .…”
Section: In Vitro Hypoglycemic Studiessupporting
confidence: 91%
“…Other phytochemical compounds, curcumin and silymarin have been recognized as powerful antioxidants. They have been found to inhibit AGEs formation in in vitro and diabetic animal models [32][33][34].…”
Section: Experimental Groupsmentioning
confidence: 99%
“…Trapping of α-dicarbonyl compounds under physiological conditions has been studied widely, and it has been shown that α-dicarbonyl compounds react with certain positions on the phenol ring via electrophilic aromatic substitution [21,22]. Catechins [22,23], curcumin [24], daidzein [25], genistein [25,26], theaflavins [23], phloretin [27], phenolic acids [28], fruit and vegetable seed extracts [29] have been shown to trap dicarbonyl compounds. Effect of phenolic compounds on trapping α-dicarbonyl compounds during food processing was focused mainly on flavor development [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%